Editorial - Ivan Čuk (University of Ljubljana Press (Založba Univerze v Ljubljani), 2020)
Dear friends, Our expectations to celebrate the highest achievements in gymnastics at the Olympic Games in  Tokyo have been postponed for a year. I hope we will be able to enjoy the Games next year. Who would have thought that one small micro size organism can stop the whole world! Some countries cancelled all sport activities, some still do let them run. Our human race is being tested. Let's hope our families, friends and everyone else will come through this crisis without any serious problems. On the other hand, we still attend to our day-to-day activities that make our days happier. Prof. Anton Gajdoš, our collaborator on history topics and friend, has just celebrated his 80th birthday. Advanced age from some people's perspective, but Anton is still full of energy. In this issue we learn a bit more about his history diaries. We wish him many happy and healthy years to come! For this issue our authors researched many different topics. I'm very pleased that we probably have the first research paper on the definition of aesthetic movement. In art it is believed that beauty is in the eye of the beholder. Pia Vinken and Thomas Heinen from Germany tried to define what aesthetic movement  in gymnastics is supposed to be (content, no errors). Ludwig Friderich Jahn would be proud of them.  For the first time we present articles from the Democratic People's Republic of Korea and Indonesia.  One article is about modelling the Jurchenko vault and another is about aerobic fitness in relation to diet. The remaining five articles were contributed by authors from Germany (judging trampolining, motor control), Portugal (morphologic characteristics), Mexico (psychology), United Kingdom and Australia (acrobatics). All together, there are eight very interesting articles in this issue. Anton Gajdoš  provides a short historical note on Professor Vladimir Ivanovič Silin of Russia. Just to remind you, if you quote the Journal, its abbreviation on the Web of Knowledge is SCI GYMN J.   I wish you pleasant reading and a lot of inspiration for new research projects and articles,​​​​    ​​​​​​​​​Ivan Čuk, Editor-in-Chief